Impact of EGF, IL28B, and PNPLA3 polymorphisms on the outcome of allograft hepatitis C: a multicenter study. Issue 4 (1st March 2016) - Mueller, Jessica L.; King, Lindsay Y.; Johnson, Kara B.; Gao, Tian; Nephew, Lauren D.; Kothari, Darshan; Simpson, Mary Ann; Zheng, Hui; Wei, Lan; Corey, Kathleen E.; Misdraji, Joseph; Lee, Joon Hyoek; et al.
Abstract: Hepatitis C virus (HCV) infection is accelerated following liver transplantation (LT). Single nucleotide polymorphisms (SNPs) near the epidermal growth factor ( EGF ) (rs4444903), IL28B (rs12979860), and PNPLA3 (rs738409) loci are associated with treatment response, fibrosis, and hepatocellular carcinoma in non‐transplant hepatitis C, but allograft population data are limited. We sought to determine the role of these SNPs in 264 patients with HCV who underwent LT between 1990 and 2008. Genotypes were determined from donor wedge/allograft biopsies and recipient explants. Cox proportional hazards model was used to assess time to cirrhosis, liver‐related death, and retransplantation, adjusting for donor age and sustained virological response (SVR). Over a median follow‐up of 6.3 yr, a trend toward increased progression to graft cirrhosis was observed among recipients of an EGF non‐AA vs. AA donor liver (adjusted HR 2.01; 95% CI 0.93–4.34; p = 0.08). No other genotypes predicted cirrhosis development or graft survival. The CC IL28B variant in both recipients and donors was associated with increased rate of SVR (R‐CC/D‐CC 8/12[67%], R‐non‐CC/D‐CC or R‐CC/D‐non‐CC 23/52[44%], R‐non‐CC/D‐non‐CC 12/45[27%], p linear trend = 0.009). Recipient EGF, IL28B, and PNPLA3, and donor IL28B and PNPLA3 genotypes do not predict adverse outcomes in HCV LT recipients. A potential association exists between donor EGF genotype and cirrhosis.